Învăţământul românesc 1948–1989 – între derivă şi recuperare institutional-funcţională - Rădulescu, Dan Constantin (Calitatea Vieții, 2006)
The study evidentiates the special importance given to the population free access to education by the totalitarian regime, in Romania, after 1948. Due to larger and larger yearly budget funds alocated to education, mainly between 1950–1980, there were made significant progress for the education process – more schools, more professor, but, the most important among all, more pupils. Nevertheless, the 1948 education law, because of its stalinist nature, alterated many actions and efforts within the education process, so, finally, the authorities had been convinced to pass a new law. That happened in 1968. The new law could restore the old good Romanian traditions as existing before 1948, along with the latest findings in education and pedagogy. But the dramatic effects of the economic collapse, as registered after 1980, has put the education system in Romania in a difficult situation, worsened, after 1989, by the general post-december crisis.